Perancangan Sistem Pengelolaan Air Hujan dengan Zero Run Off System di RSUD Kota Bogor - Ihsani, Nanda Nashiha; Setiawan, Budi Indra; Saptomo, Satyanto Krido (JURNAL TEKNIK HIDRAULIK, 2024)
Annual flooding during the rainy season at the Bogor City Regional General Hospital since 2016 has created a significant issue, potentially triggering a domino effect impacting the hospital, its visitors, staff, and patients. This study aims to design a rainwater management system to mitigate excessive rainwater puddles, which causes flooding, using the Zero Runoff System (ZROS) concept. The ZROS concept focuses on establishing an eco-drainage system for this government-owned hospital to address the issue of inundation effectively. This study employs rainfall-runoff modeling with statistical methods such as Distribution Testing and Chi-Square Analysis to determine data fit. Hydrological analysis is conducted to calculate design discharge and runoff volumes that can be discharged to detention ponds. The results show that the required storage volume is 72.35 m³, leading to the recommendation of constructing a detention pond system. The proposed detention system consists of two ponds, each measuring 5 m x 3 m with a depth of 2.5 m, providing a total storage capacity of 75 m³ to meet the required runoff control needs. The implementation of this system is expected to provide an integrated solution related to the flood issue at the Bogor City Hospital, considering that the hospital is a public facility that is prone to piles of garbage, for example, a control tub is made before water enters the Detention Pond. The chamber includes a trash screen with a closable outlet to facilitate maintenance and ensure the detention ponds remain effective. Keywords:  detention ponds, flood control,  inundation, rainwater management, zero run-off system